Pengaruh Pupuk Kandang Sapi Dan Pupuk Urea Terhadap Pertumbuhan dan Produksi Tanaman Sawi (Brasisca juncea L.) - Apelius Gulo; Ida Zulfida; Yelfi Yana Linda Br Sijabat (UNIVERSITAS LABUHANBATU, 2023)
Mustard greens (Brassica juncea. L) is one of the horticultural crop commodities from a type of vegetable that is used for its young leaves, as vegetable food and has various benefits and uses. This study used a randomized block design (RBD) with two treatment factors with 3 replications, namely: Factor I: Administration of Cow Manure (P), which consisted of 3 levels, namely: P0 = 0 kg/plot (Control), P1 = 1 kg/ plot (10 tons/ha), and P2 = 2 kg/plot (20 tons/ha), while Factor II: Administration of Urea (U) consisting of 3 levels namely: U0 = 0 g/plot (Control), U1 = 15 g/plot (150 kg/ha), and U2 = 20 g/plot (200 kg/ha). Parameters observed included plant height (2mst, 3mst, and 4mst), number of leaves (2mst, 3mst, and 4mst), root length, root volume, wet weight per sample, and wet weight per plot. The results showed that the effect of giving cow manure at 2 weeks old had an effect on increasing the number of plant leaves, but had no effect on plant height, root length, root volume, wet weight per sample and wet weight per plot. The application of Urea fertilizer had no effect on plant height, number of leaves, root length, root volume, wet weight per sample and wet weight per plot. The interaction effect of cow manure and urea fertilizer did not affect plant height, number of leaves, root length, root volume, wet weight per sample and wet weight per plot.